2020
DOI: 10.1111/cpf.12621
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of a ramping protocol to measure cerebral vascular reactivity using functional magnetic resonance imaging

Abstract: Though individual differences in arterial carbon dioxide and oxygen levels inherently exist, the degree of their influence on cerebral vascular reactivity (CVR) is less clear. We examined the reproducibility of BOLD signal changes to an iso‐oxic ramping PetCO2 protocol. CVR changes were induced by altering PetCO2 while holding PetO2 constant using a computer‐controlled sequential gas delivery (SGD) device. Two MRI scans, each including a linear change in PetCO2, were performed using a 3‐Tesla (3T) scanner. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…Regarding CVR reliability, the whole-brain average reliability of SE-MPR was comparable to long-term reliability (days or weeks apart) found in previous studies of CVR induced by BH ( Peng et al, 2019 ), by paced deep breathing ( Sousa et al, 2014 ), or by gas challenges ( Leung et al, 2016 ), and higher than that reported in other studies on BH induced CVR estimated with a non-lagged optimized P ET CO 2 hrf trace ( Lipp et al, 2015 ) or with Fourier modelling ( Pinto et al, 2016 ), and by gas challenges ( Dengel et al, 2017 ; Evanoff et al, 2020 ). Consequently, the reliability of CVR estimates obtained with the optimal combination dataset and conservative ME-ICA modelling approaches were found higher than those previously reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Regarding CVR reliability, the whole-brain average reliability of SE-MPR was comparable to long-term reliability (days or weeks apart) found in previous studies of CVR induced by BH ( Peng et al, 2019 ), by paced deep breathing ( Sousa et al, 2014 ), or by gas challenges ( Leung et al, 2016 ), and higher than that reported in other studies on BH induced CVR estimated with a non-lagged optimized P ET CO 2 hrf trace ( Lipp et al, 2015 ) or with Fourier modelling ( Pinto et al, 2016 ), and by gas challenges ( Dengel et al, 2017 ; Evanoff et al, 2020 ). Consequently, the reliability of CVR estimates obtained with the optimal combination dataset and conservative ME-ICA modelling approaches were found higher than those previously reported in the literature.…”
Section: Discussionsupporting
confidence: 80%
“…average CVR value across sessions and within subjects) ( Lipp et al, 2015 ; Magon et al, 2009 ). Both short and long term reliability of BH-induced CVR were found to be comparable to that of other non-invasive means of estimating CVR, such as resting state fMRI ( Liu et al, 2017 ), inhaled gas challenges ( Dengel et al, 2017 ; Evanoff et al, 2020 ; Leung et al, 2016 ), Fourier modelling of a BH task ( Pinto et al, 2016 ), and a paced deep breathing task ( Sousa et al, 2014 ).…”
Section: Introductionmentioning
confidence: 68%
“…Consequently, the reliability of CVR estimates obtained with the optimal combination dataset and conservative ME-ICA modelling approaches were found higher than those previously reported in the literature. However, all strategies produced a reliability that was lower than the short-term (within-session) reliability reported in BH induced CVR (Peng et al, 2019), resting state based CVR (P. Liu et al, 2017), and gas challenge induced CVR (Leung et al, 2016), although lower intersession reliability in gas challenges has also been reported (Dengel et al, 2017;Evanoff et al, 2020). Note that the reliability observed in this study seems to be globally higher and spatially less variable than that reported in previous studies (Lipp et al, 2015;Sousa et al, 2014).…”
Section: Discussioncontrasting
confidence: 78%
“…Regarding CVR reliability, the whole-brain average reliability of SE-MPR was comparable to longterm reliability (days or weeks apart) found in previous studies of CVR induced by BH (Peng et al, 2019), by paced deep breathing (Sousa et al, 2014), or by gas challenges (Leung et al, 2016), and higher than that reported in other studies on BH induced CVR estimated with a non-lagged optimized P ET CO 2 hrf trace (Lipp et al, 2015) or with Fourier modelling (Pinto et al, 2016), and by gas challenges (Dengel et al, 2017;Evanoff et al, 2020). Consequently, the reliability of CVR estimates obtained with the optimal combination dataset and conservative ME-ICA modelling approaches were found higher than those previously reported in the literature.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation